The Association Between Quality and Safety Climate of a Hospital Ward, Family Members' Empowerment, and Satisfaction With Provided Care. Issue 6 (28th May 2021) - Burlakov, Nataly; Rozani, Violetta; Bluvstein, Irit; Kagan, Ilya
Abstract: Purpose: This study was designed to examine the perceptions of ward quality and safety held by family members and nurses, and investigate its impact on family members' empowerment, and satisfaction with patient hospitalization. Design: A cross‐sectional study on two study groups was conducted at a large public hospital in Israel. The first group comprised 86 family members of patients hospitalized for more than 72 hours in acute critical condition in intensive care units (ICU) or general wards (GW). The second group included 101 registered nurses who treated the patients in the ICU or GW. Methods: Data were collected by a validated self‐administered structured questionnaire. All participants voluntarily signed an informed consent and answered questions related to their demographic characteristics, perceptions, and attitudes toward quality and safety climate, empowerment, and satisfaction with the patients' hospitalization. Pearson correlations coefficient, t‐test for independent samples, and a multiple regression model were performed to analyze the data. Findings: The mean age of family members was 51.4 ± 14.1 years and of nurses was 40.9 ± 9.9 years. A significant positive association was found between ward quality and safety climate and empowerment of the family member ( r = .716; p < .001); empowerment of the family member and family members' satisfaction with the patients' hospitalization ( r = .695; p < .001); and ward safety and quality climate and family members' satisfaction with the patients' hospitalization ( r = .763; p <.001). Family members ranked ward quality and safety climate ( M = 4.20 ± 0.60 vs. M = 3.61 ± 0.40), and their satisfaction with the patients' hospitalization ( M = 4.49 ± 0.69 vs. M = 4.07± 0.54), which were significantly ( p < .001) higher than the nurses' estimate. The significant predictors for family members' satisfaction with patients' hospitalization were commitment to quality leadership ( b = .210; p = .027); implementing a quality improvement ( b = .547; p < .001); and hand‐off communication ( b = .299; p = .001). Conclusions: Positive relationships between quality and safety climate, empowerment, and satisfaction with patients' hospitalization suggest that by improving the ward quality and safety climate, and family empowerment, we may also improve family satisfaction. Although family members reported being satisfied with hospitalization in the ICU and GW, quality leadership and implementing a quality improvement among the nurses and hand‐off communication between nurses and patients' families, will be targeted to improve family satisfaction with the patients' hospitalization. Clinical Relevance: Nurses who provide care for patients in a critical condition should maintain high levels of safety and quality care in order to improve the patients' family empowerment and satisfaction. Specifically, their efforts should target a commitment to quality leadership, implementing quality improvement, and hand‐off communication.